Professional football in times of COVID-19: did the home advantage effect disappear in European domestic leagues? - Almeida, C. H.; Leite, W. S. (Biology of Sport, 2021)
This study aimed to examine how the home advantage (HA) and home teams` performances changed in European football leagues (German Bundesliga, Spanish La Liga, English Premier League, Portuguese Primeira Liga and Italian Serie A) with the measures imposed by legal authorities to deal with the COVID-19 pandemic (no audience, five substitutions and "cooling breaks"). The HA (Pollard`s rescaled method) and home performance-related statistics of matches contested before (n = 491) and after (n = 491) the 2019-2020 season break were calculated and compared, for each league and for all five, using the paired t-test or the Wilcoxon signed-rank test. Overall, the HA did not significantly decrease in European leagues (from 16.4% to 11.6%; trivial effect size [ES]); however, a one-sample t-test revealed that the HA after the COVID-19 break was significantly greater than 0% (small ES). While the HA completely disappeared in the Bundesliga (large ES), its effects remained stable in La Liga (small ES), Premier League and Primeira Liga (trivial ES), and even increased in Serie A (medium ES) after the return. Home teams` performances in these leagues were influenced to different extents by the COVID-19 situation, especially by playing behind closed doors. Altogether, significant decreases were observed for total shots, tackles (medium ES), shots on target and pass success (small ES). Therefore, the role of crowd support seems to vary depending on the context characteristics in which football is played. Also, the augmented "information transfer" from coaches to players during COVID-19 matches might have masked the crowd effects on the HA.